COSMOPOLITAN WORLD IN CONTEMPORARY ASIA: A PHENOMENON OF ASIAN DIASPORA - Ariska, Maudi; Risman, Helda (PEOPLE: International Journal of Social Sciences, 2020)
In the world challenge moving towards modernism era, western culture endorses the “cosmopolitan” ideas to fuse into the whole system of the global world. However, multiculturalism concept argued as one of the challenges to pursue a cosmopolitan world form due to its complexity. Otherwise, while dealing with domestic issues, Asian countries are viewing multiculturalism in different perspective related to the idea of cosmopolitanism itself. The problem is, western seems hard to accept this fact or even to understand it. Western tends to criticize and highlights the problems of Asian diaspora as one of the obstacles on the towards a more cosmopolitan world. Furthermore, many issues like racial issues, gender, norms and values are always became the “unfinished business” still looking for proper solutions. Yet, there this Eastern society which is capable of conforming, and co-existing within the western sarcasm towards them. Set in phenomenology method, this paper analyze the Cosmopolitan itself according to the western perspective, and multiculturalism phenomenon itself by using multiculturalism of Bhiku Parekh’s perspective, and diaspora phenomenon, this paper seeks to offer some hypothesis of contra-productive preferences of the cosmopolitan world. This paper portrays discrepancy among values and norms of western discourse to pursue their goal through cosmopolitanism ideas.